Biofuels (Bioethanol, Biodiesel,and Biogas) from Lignocellulosic Biomass :A Review (Journal of University of Babylon for Engineering Sciences, 2020)
Gaseous emissions are from the use of fossil fuels when burned to cause an increase in global warming. Therefore, for sustainable development, consideration should be given to the production of green alternative energies that can be produced from the bio-waste available from food residues, agricultural residues or food factory residues. Converting waste to alternative energies or biofuels is a positive aspect due to the continuous increase in waste that creates environmental problems and traditional methods of waste disposal such as landfills or incineration produce gas.  Biofuels production from lignocelluloses materials which are containing carbohydrate polymers and lignin, both of these components considered as a feedstock for produce chemical material, biofuel, biomethane, biohydrogen as alternatives of fossil fuel.  In this paper, the researcher reviewed different pretreatments methods and recent technology that can be enhanced degradable of various biowaste or lignocelluloses biomass (agricultural waste, food residue, municipal wastes, and animal waste of) and conversion to biofuel (bioethanol, biodiesel, and biogas). The selection of the pretreatment of cellulosic material depends on the economic cost of producing biofuels; so many researchers around the world were trying to develop alternative energy (biofuel) production technology as an alternative to fossil fuels by reducing the economic cost of biowaste pretreatment.